Utilization of Geographic Information Systems in Environmental Vulnerability Mapping to Tsunami Disaster in West Aceh District - Azis, Daska; Abdi, Abdul Wahab; Furqan, M. Hafizul; Akbar, Wahyu (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Indonesia is a region that is vulnerable to earthquake and tsunami disasters. As a mitigation effort a disaster vulnerability map is needed. This study aims to produce a tsunami vulnerability map of the environment by implementing a geographic information system (GIS) in Aceh Barat District. Tools and materials used are: 1) computer device assisted by ArcGis Software version 10.4.1. 2) Parameter map (Land use map in West Aceh District, Map of river border distance, Beach border distance, Map of Aceh Barat District elevation map, West Aceh District slope map). Data were analyzed by scoring and weighting with overlay techniques. The results showed that the area with a very high vulnerability category was at the mouth of the river and the area of ​​the Woyla River, Bubon River, and Meureubo River with an area of ​​up to 10 . Areas with a very low vulnerability category are in the Sungai Mas and Pante Ceureumen Districts with an area of ​​1611.. Suggestions in this research are the need for more specific mapping, such as mapping of social, economic, and physical vulnerability, so that the impact of the tsunami disaster from various vulnerability factors can be minimized